Parler en écrivant: le lexique des internautes français - Gajos, Mieczysław (Verbum – Analecta Neolatina, 2006)
On-line "chat" communication combines elements of speech and writing. Specific lexical forms arise which characterize such cyberspeech. The paper provides an analysis of lexical forms underlying the discourse of on-line chats. It also attempts to answer the question of whether native forms of on-line communication should be tackled as part of foreign language teaching.